FACTORS INFLUENCING COFFEE CONSUMPTION DECISIONS AMONG YOUNG ADULTS IN PHNOM PENH - Mit, Mom (Srawung: Journal of Social Sciences and Humanities, 2024)
Coffee is the most popular beverage in the world, and coffee culture in Cambodia is gaining popularity among young adults in Phnom Penh. Many drink coffee to reduce stress or refresh their minds, while others consume it to generate energy for their entire workday. This study investigates the factors influencing coffee consumption among young adults in the capital city of Cambodia. It aims to fill a gap in the existing knowledge, as research in this area has been limited. Additionally, the study seeks to create competitive advantages in the coffee beverage industry, particularly for small business enterprises. Quantitative methods were used to address a larger population and gather quantifiable data, producing more reliable results than qualitative methods. The findings showed that brand image, price, taste, and atmosphere influenced coffee buying intention. Among these, taste was the biggest factor. The intention to buy coffee then strongly influenced the actual purchase decision.